Indonesian Muslim Intellectual Ulama in the 17th and 18th Centuries - Nurbuana, Nurbuana; Ismail, Fajri; Sukardi, Ismail; Zuhdiyah, Zuhdiyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the role of Nusantara scholars in spreading Islamic teachings, tarekat, sharia, and tasawuf, as well as their contribution to the renewal of Islamic thought in Indonesia. The research method used is qualitative with a library research approach. Data collection techniques by understanding and studying theories from various literature related to the literature such as books, journals and studies that have been conducted. The results of the study show that Indonesian scholars in the 17th and 18th centuries played a major role in building international scientific networks, transmitting ideas of Islamic renewal, and producing influential written works. This scientific tradition is not only textual, but also contextual by accommodating local elements and building a social base through Islamic educational institutions.